Urgensi Penerapan Hukuman Jinayat Mati Terhadap Pelaku Tindak Pidana Di Indonesia Dalam Perspektif Hukum Islam - Eva Diah Pitaloka; Lili Kartika; Baidhowi (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2022)
The application of the death sentence on criminals often remains a problem, questioning the urgency of the execution with inhumane significance. But in reality the death penalty in Indonesia has arranged to be issued on death certificates for specific crimes only. In islamic law the death sentence itself is a just punishment or qishas with a purpose for the betterment of society. The death penalty was given either by law or by enrollment in islamic law for the purpose of enunciating. The purpose of this writing was to discuss the history of the death penalty along with the corresponding criminal form and the islamic law's view of execution. The methods used were literature literature literature with data of legislation, expert opinion and verses of the Koran. The study results in that the death penalty can be applied or allowed in full compliance to the requirement that a criminal act be banned and that the concession arrangement in other words corresponds to what it does because it violates the rules of society.